FAKTOR-FAKTOR YANG MEMPENGARUHI KEPERCAYAAN (TRUST) PENGGUNA INTERNET DALAM BERTRANSAKSI ONLINE - Adliyani, Nurlita; Marsono, Marsono (Diponegoro Journal of Accounting, 2013)
Nowadays, the Internet became a popular medium for doing business. More and morepeople accessing the internet, especially on sites that provide space for transactions of a product.Trading over the Internet requires high trust of the consumer against the seller. The research wasused to tested the factors that influence consumer's trust in online transaction. Structural assuranceis one of the factors considered to affect consumer's confidence. In addition, the web vendorreputation is also considered as an important factor before making an online transaction.Consumer's experiences in the past in doing transactions online as well affecting consumer'sconfidence in the retailer.The population used in this study were students at the Diponegoro University. Studysample totaled 80 respondents, who had dealings over the internet, taken from five differentfaculties. Analysis tool that used is multiple regression.The result of this study has shown that the structural assurance has a positive andsignificant impact on the confidence of Internet users in the e-commerce system. Positive influenceand significance is also indicated by the effect of experience in transacting online in the past on thelevel of trust in e-commerce, with the direction of the positive regression coefficients. While, thereputation variable indicated by the positive regression coefficients with significance value isgreater than the significance level a=0,05. This means there is the vendor reputation has a positivebut not significant impact on trust in e-commerce system.